PREPARATION OF TABLE TENNIS PLAYERS WITH PROGRAMMED LEARNING ELEMENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The article discusses the usefulness of the elements used in the principles of programmed training of table tennis players. The ways of implementing such elements in the tabletop training system are shown.